2016
DOI: 10.1007/s10940-016-9306-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the Configuration of the Street Network Influence Where Outdoor Serious Violence Takes Place? Using Space Syntax to Test Crime Pattern Theory

Abstract: Objectives To examine the effect of the physical layout of the street network on the spatial distribution of outdoor serious violence. Crime pattern theory predicts crime would be more prevalent on more connected, accessible or traveled street segments, as these will be more likely to fall within an offender's awareness space.Methods The distribution of incidents of outdoor murder, attempted murder and other near-lethal violent crimes that occurred in one London (UK) borough (N = 447 offenses) was analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 49 publications
(42 reference statements)
3
65
1
Order By: Relevance
“…Principal roadway . Prior research has found that the characteristics of street networks can generate crime, with more frequently used streets presenting potential offenders with more crime opportunities than less busy streets (Davies & Johnson, 2015; Summers & Johnson, 2017). Each street segment was coded either as a principal roadway (coded as “1”) or as part of another roadway classification (coded as “0”).…”
Section: Methodsmentioning
confidence: 99%
“…Principal roadway . Prior research has found that the characteristics of street networks can generate crime, with more frequently used streets presenting potential offenders with more crime opportunities than less busy streets (Davies & Johnson, 2015; Summers & Johnson, 2017). Each street segment was coded either as a principal roadway (coded as “1”) or as part of another roadway classification (coded as “0”).…”
Section: Methodsmentioning
confidence: 99%
“…Outside of the public transportation system, the configuration of transportation routes for private vehicles could influence crime. For example, violent crimes tend to occur more on streets that are more accessible (8,82). One study by Zavoski et al (90) evaluated the impact of a single street barrier constructed by the Hartford Housing Authority in response to a drive-by shooting that wounded four teenagers near a large housing project.…”
mentioning
confidence: 99%
“…First, the data of housing boundary are only used as a spatial constraint in the article, without considering the information of spatial structure, which is one of the important factors of the social environment, and further study can focus on the usage of housing boundary as space syntax [21,[45][46][47]. Second, due to the sensitivity of data, the thematic attributes available for analysis is limited to household density, and more data related to residential burglary should be collected in the future, mainly covering the following categories.…”
Section: Discussionmentioning
confidence: 99%